Determinants of effective organisational capacity training: lessons from a training programme on health workforce development with participants from three African countries - Woldekidan Kifle Amde; Bruno Marchal; David Sanders; Uta Lehmann (BMC, 2019)
Abstract Background Health systems in sub-Saharan Africa face multifaceted capacity challenges to fulfil their mandates of service provision and governance of their resources. Four academic institutions in Africa implemented a World Health Organisation-funded collaborative project encompassing training, curriculum development, and partnership to strengthen national leadership and training capacity for health workforce development. This paper looks into the training component of the project, a blended Masters programme in public health that sought to improve the capacity of personnel involved in teaching or management/development of human resources for health. The paper aims to explore factors influencing contribution of training to organisational capacity development. Methods We chose a case study design. Semi-structured interviews were held with 18 trainees that were enrolled in the training programme, and who were affiliated to health ministries or public health training institutions. We gathered additional data through document reviews, observation, and interviews with 14 key informants associated with the programme and/or working in the collaborating institutions. The evidence gathered were analysed thematically. Results Thirteen of the 18 training participants stayed in the target institutions and contributed to improved capacity of their institutions in the fields of management, policy, planning, research, training, or curriculum development. Five left for private and international agencies due to dissatisfaction with payment, work conditions, or career prospect. Factors that were associated with the training, trainees, and the institutional and broader context, determine contribution of training to organisational capacity development. These include relevance of newly acquired knowledge and skills set of trainees to the role/position they assume in the organisation; recognition of trainees by employing organisations in terms of promotion or assignment of challenging tasks; and motivation and retention of trained staff. Conclusion Training, even if relevant and applicable, makes no more than a 'latent' contribution, one which is activated and realised through alignment of clusters of interacting contextual and relational factors related to the target institutions and trained personnel. While not predictable, implementers need to focus more deliberately on the likely interaction and best possible alignments between training relevance, student selection for potential to contribute, recognition and career advancement potential.